If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + -22 = 30 Reorder the terms: -22 + 4t = 30 Solving -22 + 4t = 30 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + 4t = 30 + 22 Combine like terms: -22 + 22 = 0 0 + 4t = 30 + 22 4t = 30 + 22 Combine like terms: 30 + 22 = 52 4t = 52 Divide each side by '4'. t = 13 Simplifying t = 13
| t^3-9t^2=0 | | 22-5n^12=22+15n^13 | | ln(x+6)+ln(4)=ln(10) | | 6y^2+13y-5=0 | | 4-6p-2p=3 | | 2(13t-15)+3(t-19)=0 | | 4x-10+2x=3(5x-5)+2 | | x=-9x^2+x+10 | | -2(2+x)=7(-3x-1) | | -25+10c^2=c^2 | | 3x+2.6=x+24 | | 5+6(-1)= | | 2h^2-7h-1= | | 15x-6.3=0 | | g^2+3g= | | 4t^2+8t= | | -7(x-1)=-4(x+7) | | -2x+7=9x+3 | | 5+6z= | | x/5=17 | | .25(y-b)=m | | 3t+5=-15 | | 5-2x=3+3x-4x | | 8x+10-(2x+5)=-55 | | -2(m-60)=-m | | 5m=3m+6 | | 9x=2x^2-18 | | 8x-12=15x+10 | | 6x+12=-6 | | 4+p^2+12p=0 | | 2(x-3)=x+9 | | X^2+7x-38=0 |